론 뮤익의 조각에 나타난 삶과 죽음의 미학 - 정연이; Chung Youn Yee (기초조형학연구, 2022)
론 뮤익은 태어나서 죽을 때까지 끊임없이 순환하는 인간의 삶을 깊이 통찰하는 조각가이다. 이 연구는 생성과 소멸, 순간과 영원, 현존과 부재에 대해 질문하는 론 뮤익의 조각에 나타난 삶과 죽음 주제의 미학적, 철학적, 사회적 의미를 고찰하는 것을 목적으로 한다. 연구를 위한 이론적 방법으로 바니타스, 지그문트 프로이트의 언캐니 개념과 줄리아 크리스테바, 조르주 바타이유, 안드레아스 후이센의 논의를 참고하였다. 첫째, 론 뮤익의 조각은 탄생과 죽음을 언캐니한 방식으로 드러낸다. 언캐니(uncanny)는 프로이트가 확장 발전시킨 이론으로 억압된 것이 회귀할 때 발생하는 친숙하지만 낯선 감정을 의미한다. 언캐니의 미적 전략은 관습적인 시각으로 놓치기 쉬운 사물을 새롭게 바라보게 하며 의식과 무의식의 경계를 자유롭게 횡단함으로써 인식의 지평을 확장한다. 둘째, 론 뮤익은 삶과 죽음을 순환하는 과정으로 받아들이며 공존하는 것으로 여긴다. 이러한 점은 이원론적 세계관을 해체하고 다양한 존재를 인정하며 공존의 담론을 이끌어 낸다. 셋째, 100개의 거대한 개별 인간 두개골로 이루어진 <덩어리>는 공동체적, 사회적 죽음을 보편적으로 시각화하며 예술에서 애도, 기억, 역사를 표현하는 미학적 가능성을 제시한다. 바니타스 정물화의 단골 소재로 등장했던 해골은 일차적으로 죽음을 상징하지만 역설적으로 재생과 풍요를 이차적으로 상징하기도 한다. <덩어리>는 전시장 전체 공간을 조각적 대상으로 활용하며, 소리와 움직임을 통해 관람자의 사유를 이끌어낸다. 또한, 과거와 현재가 교차하면서 지금 여기에 균열을 일으키며 조각의 시공간성을 확장시켜 조각의 패러다임을 새롭게 제시한다. 본 연구를 통해 삶과 죽음의 관계를 숙고하고, 인간의 실존에 대해 사유하는 론 뮤익의 독창적인 예술 세계를 입체적으로 조명할 수 있었다. Ron Mueck is the sculptor who penetrates profoundly the life of human circulating constantly from birth to death. This research aimed to consider the aesthetic, philosophical, social meanings of life and death theme in the sculpture of Ron Mueck asking the formation and extinction, moment and immortality, and present and absent. As a theoretical method for the study, Vanitas, Sigmund Freud’s uncanny concept, Julia Kristeva, Georges Bataille, Andreas Hyssen’s argument were referred. First, the sculpture of Ron Mueck reveals the birth and death as uncanny method. Uncanny that extended and developed by Freud means the familiar but strange emotion that occurs when the repressed returned. The concept of uncanny within Ron Mueck’ sculpture represents through the visual methodology of defamiliarization which occurs through expansion and reduction of object’s scale. The aesthetic strategy of uncanny contemplates newly objects that can be easily missed with a customary vision and extends an area of perception by freely traversing borders between consciousness and unconsciousness. Second, Ron Mueck accepts the life and death which circulate and coexist. This dismantles dualistic world view and recognizes various existence and leads the discourse of coexistence. Third, the < Mass > which is composed of huge 100 individual human skulls visualizes generally a communal, social death and presents the aesthetic possibility which expresses the mourning, memory, history, in art. The skull which appeared the regular material of the vanitas still-life painting symbolizes the death primarily, but paradoxically, reproduction and abundance secondary. The < Mass > utilizes a whole space of exhibition as a sculptural object and brings out the thinking of viewer through sound and movement. and it makes a fissure here and now intersecting past and today and presents the new paradigm of sculpture by expanding the space and time of sculpture. This study viewed three dimensionally the creative art world and the aesthetic effect of work of Ron Mueck pondering the relationship between life and death and thinking the existence of human.